Misuse of Ozempic as a drug choice for weight loss, a potential threat - Aslam, Uzma; Mehboob, Sarah (International Journal of Scientific Reports, 2023)
The 387 million people around the globe are diagnosed with type 2 diabetes mellitus (T2DM). Previously used agents to treat T2DM posed adverse risks of hypoglycaemia and weight gain. Recently, Novo Nordisk, a pharmaceutical company, launched a new drug, Ozempic (Semaglutide), a glucagon-like peptide-1 receptor agonist (GLP-1 RA), which was approved by the US Food and Drug Administration on December 5, 2017. The numerous benefits of Ozempic makes it ideal for treatment of T2DM. Unfortunately, there is now an alarming shortage of Ozempic due to its misuse for weight loss.